Evaluar la eficacia de sellantes realizados con la técnica Art en las escuelas "Ángel Isaac Chiriboga" (La Vicentina) y "Jacinto Collahuazo" (Cocotog) - Castro Vaca, Jennifer Valeria (2014)
To evaluate the effectiveness of ART sealants of two schools, one urban and one rural, visited within the Community Service Program by the Faculty of Dentistry, Universidad de Las Americas 2010-2012. Material and methods: This study is an observational analytical design. This paper was conducted in coeducation public schools “Jacinto Collahuazo” (Cocotog) for the rural sector and “Ángel Isaac Chiriboga” (Vicentina) corresponding to the urban sector. For the evaluation, the first molars were included in the sample. These students received dental care by undergraduate students at the Universidad de las Américas in the 2010 -2012 period; taking the criteria for sealants and caries evaluation posed by Frencken. The sample was completed with 160 children (631 first molars), 127 (499 first molars) in the rural school and 33 (132 first molars) in the urban school. The collect data were organized with the program SPSS 22 and analyzed using Chi-squared (X2) test. Results: A statistically significant difference was found in relation to the presence of sealants among students in schools located in the rural sector and the urban sector. A greater loss of sealants was evidenced in the students from the school in the rural sector. There is no statistically significant difference in relation to the presence of cavities in the students located in rural and urban areas. Conclusions: The absence of glass ionomer cement sealants was high in the students of the rural area and low in the urban area; possibly attributed to "operator effect". Although, the preventive effect was present.